Quality of Life in Patients with Spinal Cord Injury Attending Selected Rehabilitation Centers of Nepal - Gautam, Pratiksha; Marasini, Rudra Prasad; Shrestha, Rosy; Gautam, Pratibha; Marasini, Laxmi (Journal of Nepal Health Research Council, 2019)
Background: Spinal cord injury is damage to the spinal cord resulting from trauma, diseases or degenerations. The aim of this study is to identify the quality of life among the patients with spinal cord injury in relation to the physical, psychological, social and environmental health. Methods: This is a cross-sectional study performed within a period of one year in 103 spinal cord injury patients in two different rehabilitation centers of Nepal by using WHOQOL-BREF through face to face interview. The quality of life had been analyzed by descriptive and inferential statistics by using socio-demographic and disease related variables. Results: The study finding revealed that the overall quality of life was impaired in spinal cord injury patients and it was more in psychological (48.17±14.99) and environmental health (38.70±13.79) as compared to physical (55.01±12.77) and social health (51.81±12.89). The mean difference of quality of life score in education (p=0.017), occupation (p= 0.003), and income status (p=0.001) was found statistically significant (p value <0.05) and the highest relationship was found between the psychological health and environmental health (r=0.668). Conclusions: More than 50%of the spinal cord injury patients had below the average quality of life. Physical health and social health scores are above the average but psychological and environmental health score are below the average. The overall quality of life of Spinal cord injury patients can be improved by modifying psychological health, environmental health, education, occupation, and income status. Keywords: Quality of life; rehabilitation; spinal cord injury patients.